BEHAVIOUR PROBLEMS OF ADOLESCENTS IN SECONDARY SCHOOLS OF BULAWAYO: CAUSES, MANIFESTATIONS AND EDUCATIONAL SUPPORT - CHIMHENGA, Dr. SYLOD (IJRDO- Journal of Educational Research, 2017)
Behaviour problems frustrate many teachers and create an unpleasant teaching and learning environment. When disruptive interactions occur between teachers and learners, these sometimes lead to a chain of actions and reactions that spiral out of control resulting in chaos in the classroom. Behaviour problems are a problem in many secondary schools in Zimbabwe. This study investigated the causes and manifestations of behaviour problems of adolescent learners and suggested guidelines for teachers on how to assist learners with behaviour problems in the classroom. This is a quantitative study that used questionnaires. The questionnaire items for this study were in the form of a four or five point Likert-Scale. The main findings contributing to the causes of behaviour problems among adolescent learners are environmental factors, such as the family and the school and peer pressure. Behaviour problems are manifested by adolescents as disruptive behaviour, aggressive and antisocial behaviour, telling lies and theft. The findings highlight important guidelines, which teachers can use to assist and understand learners with behaviour problems in the classroom. The guidelines present an endeavour to solve problem behaviour in the classroom.